Peculiarities of Modern English Educational Terminolexicon - Soroka, Tetiana (Didactica Danubiensis, 2022)
The relevance of the study lies in the feasibility of theoretical justification of new approaches to the formation and organizational and methodological support of the innovative orientation of the educational process of the school. Peculiarities of innovative activity, ways of solving the problem of readiness for innovative activity and ways of its formation were the subjects of research A. Babeshko, N. Vasylenko, I. Gavrish, N. Gorodetskaya, N. Klokar, O. Kozlova, A. Kolomiets, E. Makagon, L. Petrichenko, A. Prigozhina, V. Slastyonina, E. Sof'yants, I. Chorny and others. The study of terminology in the field of use, the terminological theory of text is a direction clearly indicated by V.M. Leichik. The approach to the study of terminology in the field of communication can be traced in the scientific researches Rubtsova N.V., Bukovskaya L.V., Fedyunina S.M., Skulovich N.B., Podkolozina T.A., Vlasova O.B., monographs and publications by Volodina M.N., Silvia Davel, Fred Riggs, Patricia Thomas. The aim of the study is to determine the patterns of formation of knowledge of English terminology in the field of "Education" by graduate students through the use of a specialized system of tasks. Research hypothesis: the specialized system of tasks aimed at developing knowledge of English terminology in the field of "Education" of graduating students will be a full-fledged tool for teaching English at school and increase the effectiveness of foreign vocabulary. To solve the above problems, the following general scientific research methods have been used: scientific deduction, systematic analysis and comprehensive study of psychological, pedagogical, linguistic and methodological literature in order to substantiate the theoretical foundations; grouping, comparison and classification units in the field of Education and determining the methodological difficulties of its assimilation by high school students; pedagogical observation, modeling of processes and situations with the purpose finding out the level of effectiveness of the formation of English lexical competence; testing of graduating students for current and final control of the level of formation of lexical competence and finding ways to improve the process of learning vocabulary; experiments.